2016
DOI: 10.1161/circresaha.115.308237
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs for Restenosis and Thrombosis After Vascular Injury

Abstract: Percutaneous revascularization revolutionized the therapy of patients with coronary artery disease. Despite continuous technical advances that substantially improved patients' outcome after percutaneous revascularization, some issues are still open. In particular, restenosis still represents a challenge, even though it was dramatically reduced with the advent of drug-eluting stents. At the same time, drug-eluting stent thrombosis emerged as a major concern because of incomplete or delayed re-endothelialization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 164 publications
(217 reference statements)
0
89
0
3
Order By: Relevance
“…Interestingly, ACS patients undergoing percutaneous coronary intervention (PCI) saw their plasma concentration of platelet MPs decrease, leading the authors to conclude that platelet MPs may be both a promising biomarker for the development of ACS and a prognostic factor of PCI. A role for microRNAs in restenosis and thrombosis after vascular injury has also been proposed [80].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Interestingly, ACS patients undergoing percutaneous coronary intervention (PCI) saw their plasma concentration of platelet MPs decrease, leading the authors to conclude that platelet MPs may be both a promising biomarker for the development of ACS and a prognostic factor of PCI. A role for microRNAs in restenosis and thrombosis after vascular injury has also been proposed [80].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…To explore the role of AGGF1 in VSMCs functions, we studied neointimal formation, a process caused mostly by VSMCs proliferation and migration 19, 21, 24, 25, 26. Immunostaining showed that AGGF1 expression was dramatically reduced in carotid arteries with neointimal formation after vascular injury (Figure 1B and 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Incidence of restenosis has been reduced to 17% to 41% with use of bare‐metal stents and further reduced to 10% with the use of drug‐eluting stents 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17. However, drug‐eluting stents presented with an unexpected problem of an increased rate of in‐stent thrombosis (0.5–3.1%),4, 5, 6, 7, 18, 19 which causes a significantly high 6.3% rate of MI and death 18, 20, 21, 22. This led to a 20% reduction in the use of drug‐eluting stents 23.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations